Prevalence of Obsessive-Compulsive Personality Disorder Symptoms and Its Association with Burnout among Family Medicine Residents in Riyadh Second Health Cluster, Saudi Arabia - Alsawah, Zainah; Al Amoudi, Sarah; Alfakhri, Mohannad M. (International Journal of Innovative Research in Medical Science, 2022)
Aim: The present study aimed at investigating the prevalence of Obsessive-compulsive personality disorder (OCPD) and the association between OCPD and burnout among family medicine residents in cluster two hospitals in Riyadh city, Saudi Arabia. Method: This was a cross-sectional study over a sample of 114 family medicine residents from hospitals at cluster two in Riyadh city. A self-administered survey consisting of the Diagnostic and Statistical Manual of Mental Disorders; (DSM-5 criteria) questionnaire for OCPD and Maslach Burnout Inventory- (MBI) were distributed over the participating family medicine residents. Results: The findings of the study indicated that OCPD was prevalent among 22.8% (n=26) of the enrolled family medicine residents. In addition, it was found that high emotional exhaustion, high depersonalization and low professional accomplishment were prevalent among 33.4% (n=38), 57% (n=65) and 93% (n=106), respectively. In addition, the study found that there was a significant association between OCPD and emotional exhaustion (p < 0.001), depersonalization (p < 0.001) and professional accomplishment (p < 0.001). Conclusion: The study concluded that there is a significant prevalence of OCPD among family medicine residents in cluster two hospitals in Riyadh city, Saudi Arabia. In addition, the study concluded that OCPD is significantly associated with burnout. The study recommended reviewing the educational and professional content of the residency program taking into consideration the mental health aspects of the family medicine residents and to perform periodical mental health assessment tests for the family medicine residents in Saudi Arabia.